2013
DOI: 10.2172/1115335
|View full text |Cite
|
Sign up to set email alerts
|

Test report : Raytheon / KTech RK30 Energy Storage System

Abstract: The Department of Energy Office of Electricity (DOE/OE), Sandia National Laboratories (SNL) and the Base Camp Integration Lab (BCIL) partnered together to incorporate an energy storage system into a microgrid configured Forward Operating Base to reduce the fossil fuel consumption and to ultimately save lives. Energy storage vendors will be sending their systems to SNL Energy Storage Test Pad (ESTP) for functional testing and then to the BCIL for performance evaluation. The technologies that will be tested are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…As it has been shown for a zinc-bromide flow battery, fire hazards can still originate from electric components such as the inverters. 26 The findings reported in this study extend the scope of the existing literature on RFBs and their reliability to the system level. It could be shown that particular attention should be paid to elements not considered in previous studies.…”
Section: F I G U R Esupporting
confidence: 70%
See 1 more Smart Citation
“…As it has been shown for a zinc-bromide flow battery, fire hazards can still originate from electric components such as the inverters. 26 The findings reported in this study extend the scope of the existing literature on RFBs and their reliability to the system level. It could be shown that particular attention should be paid to elements not considered in previous studies.…”
Section: F I G U R Esupporting
confidence: 70%
“…Thus, the probability of catastrophic damages beyond the boundaries of the RFB system itself (which might even include injuries or fatalities) is consequently low. As it has been shown for a zinc‐bromide flow battery, fire hazards can still originate from electric components such as the inverters 26 …”
Section: Resultsmentioning
confidence: 99%
“…The results shown allow for a maximum load of 100% rated capacity for each generator, although the model facilitates imposing a limit (e.g., 80%) in order to leave a spinning reserve for peak loads as done by many microgrid management systems. 13,16 Rather than underloading a generator, microgrid management software can divert excess energy generation to battery storage for use later on when generators are turned off, and batteries can serve the role of providing peak power within their discharge limits. One can also see in Figure 1 that the benefits of PV and wind turbine installations are location-specific with wind performing better in some locations and solar in others.…”
Section: Resultsmentioning
confidence: 99%
“…10 Other studies from both academic institutions and government suggest that microgrids with energy storage and scheduling management alone can reduce fuel consumption at FOBs by 20%-30%. 15,16 In addition, researchers are developing optimization models for non-military applications, such as the Food-Energy-Water Microgrid Optimization with Renewable Energy (FEWMORE), which is meant to minimize capital, maintenance, and operations costs for remote Arctic communities. 17 These studies are useful, but they are limited in that they investigate a specific scenario or package of technologies.…”
Section: Introductionmentioning
confidence: 99%